Multi-Platform Strategies of Populis Figur in West Sumatra - Lestari, Yayuk; Diego, Diego; Okditazeini, Vannyora (Semantik: Journal of Social, Media, Communication, and Journalism, 2025)
This article explores the digital strategies of Islamic populism in West Sumatra by examining how key figures such as Fauzi Bahar and Jel Fathullah systematically leverage social media platforms to disseminate moral discourses grounded in the local religious-philosophical paradigm of Adat Basandi SyaraÔÇÖ, SyaraÔÇÖ Basandi Kitabullah (ABS-SBK). Drawing on a descriptive qualitative approach through digital observation, the study reveals a multi-platform orchestration in which Facebook functions as a site for constructing long-form religious narratives and symbolic continuity, while Instagram Reels and TikTok are deployed for affective mobilization through short, emotionally charged content featuring themes such as hijrah, almsgiving, and Islamic virtue. The interplay of symbolic messaging and technical affordances across platforms illustrates what scholars have termed symbolic convergenceÔÇöa synchronization of religious rhetoric with platform-specific features to consolidate affective publics. The analysis demonstrates how figures like Jel Fathullah transform short-form visual content into emotional gateways that channel followers toward deeper ideological engagements via Facebook Live or digital sermons. User engagement through likes, shares, and comments is interpreted by followers as a form of "digital charity," signaling a shift in the mediation of moral authority from religious institutions to platform architectures and algorithms. This study argues that Islamic digital populism in West Sumatra constitutes a form of vernacular, platformized politics wherein local identity, digital aesthetics, and moral claims coalesce. It advances the understanding of how emotional resonance, identity performance, and religious legitimacy are orchestrated through hybrid media systems.